Polyelectrolytes Assembly: A Powerful Tool for Electrochemical Sensing Application - Ivana Škugor Rončević; Denis Krivić; Maša Buljac; Nives Vladislavić; Marijo Buzuk (Sensors, 2020)
The development of sensing coatings, as important sensor elements that integrate functionality, simplicity, chemical stability, and physical stability, has been shown to play a major role in electrochemical sensing system development trends. Simple and versatile assembling procedures and scalability make polyelectrolytes highly convenient for use in electrochemical sensing applications. Polyelectrolytes are mainly used in electrochemical sensor architectures for entrapping (incorporation, immobilization, etc.) various materials into sensing layers. These materials can often increase sensitivity, selectivity, and electronic communications with the electrode substrate, and they can mediate electron transfer between an analyte and transducer. Analytical performance can be significantly improved by the synergistic effect of materials (sensing material, transducer, and mediator) present in these composites. As most reported methods for the preparation of polyelectrolyte-based sensing layers are layer-by-layer and casting/coating methods, this review focuses on the use of the latter methods in the development of electrochemical sensors within the last decade. In contrast to many reviews related to electrochemical sensors that feature polyelectrolytes, this review is focused on architectures of sensing layers and the role of polyelectrolytes in the development of sensing systems. Additionally, the role of polyelectrolytes in the preparation and modification of various nanoparticles, nanoprobes, reporter probes, nanobeads, etc. that are used in electrochemical sensing systems is also reviewed.